ASSESSMENT OF COMPLIANCE TOWARDS STANDARD CURATIVE TREATMENT PROTOCOL FOR ORAL CANCER IN A UNIVERSITY SET UP - Sundara Murthy, Sindhu Priya Kuppusamy; N, Mahathi; Suresh (International Journal of Psychosocial Rehabilitation, 2019)
Decisions on the treatment of oral cancer are getting difficult, due its high morbidity rate, social class and esthetic concerns post treatment. Some patients may therefore decline standard curative treatment. The aim of the study was to evaluate the prevalence of patients accepting the standard curative treatment for oral cancer in a university hospital setting. Data was collected from case sheets of patients who reported during the months of October 2019 and March 2020 from the hospital record management system where all the records of patients regarding their medical and dental history and treatment done are stored. All the collected data were cross verified and compiled together in an excel sheet. Compiled data were statistically analysed with help of SPSS software. In this study, with a total 51 patients, 75.86% of the patients accepted and underwent the treatment. 24.14% of patients refused the standard curative protocol. 18-29 and >60 age groups, refused treatment for oral cancer, with p value of 0.066 (